2016
DOI: 10.1007/s00403-016-1681-4
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-based quantitative proteomics of stratum corneum of dandruff scalp reveals new insights into its aetiology and similarities with atopic dermatitis

Abstract: The study aimed at detecting differentially expressed proteins in the stratum corneum of dandruff versus non-dandruff scalps to better understand dandruff aetiology. iTRAQ-based quantitative proteomic analysis revealed a total of 68 differentially expressed biomarkers. A detailed analysis of their known physiological functions provided new insights into the affected metabolic pathways of a dandruff scalp. Dandruff scalp showed (1) profound changes in the expression and maturation of structural and epidermal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…Similar findings showing increased expression of KLK6 proteases have been reported. 11 The increased expression of KLK5 and KLK6 in the SC of dandruff-affected subjects agreed with reports from previous studies on atopic dermatitis. 16 In a murine atopic dermatitis model, alteration of pH induced upregulated expression of KLK5, leading to skin barrier dysfunction.…”
Section: F I G U R Esupporting
confidence: 91%
“…Similar findings showing increased expression of KLK6 proteases have been reported. 11 The increased expression of KLK5 and KLK6 in the SC of dandruff-affected subjects agreed with reports from previous studies on atopic dermatitis. 16 In a murine atopic dermatitis model, alteration of pH induced upregulated expression of KLK5, leading to skin barrier dysfunction.…”
Section: F I G U R Esupporting
confidence: 91%
“…However, even though innate immune receptors such as TLR2 have been reported to mediate Malassezia sp. cytotoxicity to keratinocytes in vitro , its detailed mechanism remains to be identified in in vivo (Donnarumma et al, 2014 ; Cavusoglu et al, 2016 ). A high abundance of pathways related to general functions and genetic information and processing (sulfur relay system, proteasome pathway, cell cycle in yeast, and meiosis) was also observed in the dandruff scalp compared to the healthy scalp, which showed a significant positive correlation with M. restricta .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that SASPase has a key role in SC barrier function. Recent proteomics studies of subjects with dandruff scalp showed that there was a significant increase of SASPase in the SC in this condition [9]. Furthermore, de novo missense variants in SASPase in dogs result in aberrant filaggrin expression and an associated ichthyosis skin phenotype [10].…”
Section: Introductionmentioning
confidence: 99%
“…Filaggrin (FLG) mutations are recognized as a major risk factor for AD [20] and mutations in the gene also underlie Ichthyosis vulgaris syndrome [21]. The protein levels of FLG2 are also decreased in the SC and epidermis of AD patients [22,23], in the SC from dandruff condition [9], in a lipid raft disruption model [24] and in ichthyosis peeling skin [19,25] suggesting that FLG2 plays an important role in epidermal homeostasis and barrier formation. In a reconstructed epidermal model where the expression of FLG2 was downregulated by lentivirus mediated shRNA interference, the levels of filaggrin processing enzymes were reduced, resulting in decreased levels of filaggrin derived free amino acids.…”
Section: Introductionmentioning
confidence: 99%